Pengembangan Sistem Informasi Pariwisata Berbasis Android - Dengo, Moh. Fadel; Dai, Roviana H.; Amali, Lanto Ningrayati; Abdillah, Tajuddin; Olii, Salahudin; Tuloli, Mohamad Syafri (Jambura Journal of Informatics, 2022)
The Pentadio Resort tourist attraction in Gorontalo Regency is a place that has uniqueness, beauty, and value in the form of natural wealth, culture, and manufactured products, which are destinations for tourism activities. Currently, information related to the facilities is not widely available. One reason is that the information provided is still manually installed on paper in a specific location. In addition, there is no medium for interaction between tourists and tour managers. This study aims to develop an application for an android-based tourism information system. The method used in this study is prototyping, which comprises five stages: communication, quick planning, quick modeling design, prototype construction, deployment delivery, and feedback. The results obtained by the application can provide information related to facilities in the Pentadio Resort attraction, such as status, warnings, prices, and location points of the facility, as well as review features as a means of interaction or reporting for tourists to the attraction manager. Objek wisata Pentadio Resort di Kabupaten Gorontalo merupakan tempat yang memiliki keunikan, keindahan dan nilai berupa kekayaan alam, budaya dan hasil buatan manusia yang menjadi tujuan untuk melakukan kegiatan pariwisata. Namun informasi berkaitan dengan fasilitas tersebut saat ini belum tersampaikan secara meluas. Satu hal yang menjadi sebab adalah informasi yang disediakan masih secara manual melalui kertas yang dipasang di tempat tertentu. Selain itu belum tersedia media interaksi antara wisatawan dan pengelola wisata. Penelitian ini bertujuan untuk mengembangkan sebuah aplikasi sistem informasi pariwisata berbasis android. Metode yang digunakan pada penelitian ini adalah Prototyping yang memiliki 5 tahapan yaitu communication, quick plan, modeling quick design, construcion of prototype, dan deployment delivery and feedback. Hasil penelitian yang diperoleh aplikasi yang dapat memberikan informasi terkait fasilitas yang ada di objek wisata Pentadio Resort seperti status, peringatan, harga dan titik lokasi dari fasilitas, serta menyediakan fitur ulasan sebagai sarana interaksi ataupun pelaporan bagi wisatawan ke pengelola objek wisata.